Managing behavioural academic self-esteem using FuzzyXteem - Siraj, Fadzilah; Tajuddin, Taniza (Universiti Utara Malaysia, 2006)
Behavioural Akademic Self-Esteem (BASE) has been used with children of preschool, elementary; and junior high school classes both individually and in groups.In this study,BASE is used to estimate the factor structures and determine the levels of academic self-esteem of the student.The current practice of the existing system using BASE scale may be scored by hand or by computer based on the rigid crisp values to represent rating number one through five.Since BASE requires the ability for estimating the factor structure and also the ability to exlpain how the conclusion is derived,therefore artificial intelligent techniques that are required to perform BASE must be able to perform estimation and provide reasoning.For this purpose fuzzy logic and expert system have been integrated in a web-based environment to demonstrate the use of hybrid system on BASE factor structure and levels of academic self-esteem.For each BASE factor, the sub score is provided based on the classifications of Academic Self-Esteem and their respective ranges.In FuzzyXteem,users in particular teachers, counselors, or parent are allowed to measure students' self-esteem at early age using real time computation.FuzzyXteem facilitates user by automatically evaluating BASE factors and help the user diagnoses their students' level of academic self-esteem in 3 ratings:low,moderate and high.It is also able to provide explanation and describe how the conclusion can be derived.The system has been successfully tested by the counselors and conforms to the BASE factor rating scale and sub-scores.FuzzyXteem can be use as an aid to decision making in improving a person's self esteem, and indirectly increases an individual for productivity.The same system functions can be applied to business organization for managing and improving the organizations performance.